2018
DOI: 10.4236/anp.2018.72004
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis Route of Au-Ag Nanostructures Soaked in PEG

Abstract: A nanostructured gold-silver soaked in polyethylene glycol 400 (Au-Ag@PEG) is designed using gold(I) chloride and silver nitrate (AgNO 3) as precursors and, polyethylene glycol 400 (PEG) as capping agent. The result of the structure characterization using Selected Area Electron Diffraction (SAED) has showed that the synthesized nanomaterial has a good crystallinity while Transmission Electron Microscopy (TEM), energy dispersive X-ray spectrometry (EDX) and Dynamic Light Scattering (DLS) measurements suggest mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The graph of resonance absorption Au@Ag NPs has two-stage in the first two peaks Ag and Au core after with an increase in the amount of AgNO 3 , the specific peak of Au@Ag NPs was established and continued (Zhong et al, 2019). The observed crystalline nature of the Au@Ag NPs was further confirmed by the TEM image (Fodjo et al, 2018;Zhong et al, 2019). XRD patterns of Au@Ag NPs have constant and alike lattice constants and no other impurity metals (no peaks).…”
Section: Discussionmentioning
confidence: 78%
“…The graph of resonance absorption Au@Ag NPs has two-stage in the first two peaks Ag and Au core after with an increase in the amount of AgNO 3 , the specific peak of Au@Ag NPs was established and continued (Zhong et al, 2019). The observed crystalline nature of the Au@Ag NPs was further confirmed by the TEM image (Fodjo et al, 2018;Zhong et al, 2019). XRD patterns of Au@Ag NPs have constant and alike lattice constants and no other impurity metals (no peaks).…”
Section: Discussionmentioning
confidence: 78%
“…The bright rings and spots corresponding to the diffraction planes (111), ( 200) and (311) of the AgÀ Au crystal, indicating that the as-synthesized NPs had high crystallization. [35] XRD, EDX, and TGA measurements were made to acquire a deeper understanding of the crystal structure and elemental composition of the as-synthesized alloy NPs (Figure 4). As shown in the X-ray diffraction pattern, the fabricated sample exhibited distinct and strong peaks demonstrating the formation of NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Selected area electron diffraction measurement showed that the Ag−Au alloy NPs were spherical. The bright rings and spots corresponding to the diffraction planes (111), (200) and (311) of the Ag−Au crystal, indicating that the as‐synthesized NPs had high crystallization [35] …”
Section: Resultsmentioning
confidence: 99%